COVID-19 pandemic: impact of lockdown and hospital classification on neurological patients - Singh, Amandeep; Goyal, Nitisha; Chouksey, Dinesh; Telang, Kapil; Jain, Rahul; Sodani, Ajoy K. (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID-19 pandemic has impacted human life by the steps taken to mitigate it. The restriction of movement and earmarking hospitals exclusively for catering to the COVID-19 patients might have affected the health of non-COVID-19 patients adversely. This study was aimed to assess the impact of lockdown and hospital classification in neurological patients. Methods: This study was conducted in the Department of Neurology in a 1000 bedded teaching hospital which has been earmarked as COVID dedicated hospital (the red hospital). The patients who attended the outpatient department and discharged from the Neurology department, prior to the lockdown, were contacted telephonically and asked to report their difficulties, if any, in the procurement of prescribed medication, medical consultation, monitoring drug side effects, and symptom control, etc. Patients were grouped into those who needed close surveillance and routine follow up. Results: Out of 1201 patients 646 could be reached. The average age of our population (n=646, female 56.4%) was 39.63±15.52 years. In the study group, the prescription breach was found in 343 patients (53.10%), management breach was in 449 (69.50%), confidence breach was in 398 (61.61%) and adverse effect on drug availability was found in 330 (53.10%) patients. In the close surveillance group (n=420), the patient's health was deemed to be at risk in 328 (78.10%) patients as compared to 161 patients (71.24%) in routine follow up group with a significant p value of 0.05. Conclusions: Our results suggest that lockdown and classification of hospitals to cater exclusively to COVID-19 patients has significantly ill-affected the health of the non-COVID subjects.